1980
DOI: 10.1007/bf01870582
|View full text |Cite
|
Sign up to set email alerts
|

Dual effects of K ions upon the inactivation of the anomalous rectifier of the tunicate egg cell membrane

Abstract: Summary. Inactivation of the K inward currentthrough the anomalous rectifier channel of the egg cell membrane of a tunicate, Halocynthia roretzi Drashe, was studied under voltage-clamp. The noise spectrum of the steady-state current recorded at hyperpolarized potentials was measured in solutions in which Na, Cs, Hydrazine, or Sr caused inactivation of the current. The unitary conductance estimated was independent of which cation caused inactivation. From the relation between the concentration of cations which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
60
0

Year Published

1983
1983
1995
1995

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(73 citation statements)
references
References 23 publications
13
60
0
Order By: Relevance
“…Furthermore inactivation upon large hyperpolarizations seems to be a regular finding for inward rectifiers of different preparations. Such inactivation in normal conditions has been shown for large hyperpolarizing steps in frog skeletal muscle by Almers (1972 a, b), in starfish eggs by Hagiwara, Miyazaki, Moody & Patlak (1978) and in tunicate eggs by Ohmori (1978Ohmori ( , 1980 and Fukushima (1981Fukushima ( , 1982. Since K depletion in a single-cell preparation is expected to be much reduced, the presence of a decay of the inward current for large hyperpolarizations could indicate that inactivation of the inward rectifier upon large hyperpolarizations can have a significant role in determining the current wave form in cardiac Purkinje cells.…”
Section: Single Cardiac Purkinje Cellsmentioning
confidence: 83%
“…Furthermore inactivation upon large hyperpolarizations seems to be a regular finding for inward rectifiers of different preparations. Such inactivation in normal conditions has been shown for large hyperpolarizing steps in frog skeletal muscle by Almers (1972 a, b), in starfish eggs by Hagiwara, Miyazaki, Moody & Patlak (1978) and in tunicate eggs by Ohmori (1978Ohmori ( , 1980 and Fukushima (1981Fukushima ( , 1982. Since K depletion in a single-cell preparation is expected to be much reduced, the presence of a decay of the inward current for large hyperpolarizations could indicate that inactivation of the inward rectifier upon large hyperpolarizations can have a significant role in determining the current wave form in cardiac Purkinje cells.…”
Section: Single Cardiac Purkinje Cellsmentioning
confidence: 83%
“…Analysis of single-channel activity in this preparation has shown that the presence of a channel blocker (i.e., Na +) is necessary to even see current fluctuations owing to channel closing (Ohmori, 1980). It has also been suggested that inactivation in skeletal muscle is at least partially due to a time-and voltage-dependent block of the inward current by extracellular Na § (Standen and Stanfield, 1979).…”
Section: Comparison Of Iki With Other Inward-rectifying K § Currentsmentioning
confidence: 95%
“…Although the mechanism is not understood, Ohmori (1980) suggested an Na + dependence for channel activation (as well as inactivation) because of the increase in apparent channel activity seen using fluctuation analysis. Fukushima (1982), however, suggested that extracellular Na + may facilitate single-channel conductance.…”
Section: Comparison Of Iki With Other Inward-rectifying K § Currentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current-voltage relations given in this paper we have subtracted a linear element (leak), by extrapolating the currents obtained for depolarizations greater than 60 mV through the holding potential (c.f. Adrian & Freygang, 1962;Adrian, 1964;Standen & Stanfield, 1978, 1980 Membrane currents in 80 mM-TI Ringer Single-pulse experiments Fig. 1 A shows membrane potential and membrane current records from a fibre immersed in 80 mM-Tl Ringer, for a hyperpolarization of 140 mV from the holding potential.…”
Section: Methodsmentioning
confidence: 99%